Chemical Composition and Insecticidal and Repellent Effect of Essential Oils of Two Premna Species against Sitotroga cerealella. (27th July 2015) - Adjalian, Elvis; Sessou, Philippe; Odjo, Théophile; Figueredo, Gilles; Kossou, Dansou; Avlessi, Félicien; Menut, Chantal; Sohounhloué, Dominique
Abstract : This work aims to study for the first time the chemical composition and evaluate insecticidal and repellent effects of essential oils of Premna angolensis and Premna quadrifolia leaves, against Sitotroga cerealella, an insect pest of rice stocks as alternatives to synthetic pesticides. The GC-MS analysis showed that essential oil of P. angolensis contains 29 compounds representing 96.1% of the oil and 42 compounds corresponding to 91% for the essential oil of P. quadrifolia . The main constituents regardless of the species were β -caryophyllene (13.1%), (E)- β -caryophyllene (13.5%), octen-3-ol (3.2%–28%), phytol (3.7%–4.9%), β -elemene (1.4%–21%), globulol (11.2%), germacrene-D (8.9%), α -humulene (2.9%–6.4%), α -pinene (5%), sabinene (3.7%), δ -cadinene (0.4%–3.3%), and linalool (3.3%). The results of laboratory tests showed that both essential oils have insecticidal and repellent effects on S. cerealella . Presenting the results, the damage caused by the adults and larvae of S. cerealella was evaluated by calculating the percentage of grains attacked and weight loss thereof. The results suggest that volatile extracts of P. angolensis and P. quadrifolia can be used as alternatives to synthetic chemicals in paddy protection against S. cerealella .